2014
DOI: 10.1002/elsc.201400080
|View full text |Cite
|
Sign up to set email alerts
|

Separation of recombinant antibodies from DNA using divalent cations

Abstract: New downstream methods for the purification of antibodies are required to meet the demands of current and future antibody applications, e.g. for mass production as cancer therapeutic. The standard chromatographic methods suffer from high material costs and mass transfer limitations. In this study, we established and characterized a method for DNA precipitation for antibody purification using divalent cations, particularly CaCl2, using four different antibodies. By implementing high‐throughput screening using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The insoluble polymer is then removed using depth filtration resulting in a low aggregate feed stream. Satzer and coworkers has recently shown that addition of calcium chloride to mAb conditioned medium containing phosphate will result in the formation of insoluble calcium phosphate that can effectively precipitate DNA . HCP and aggregate levels were also reported to be lower after treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The insoluble polymer is then removed using depth filtration resulting in a low aggregate feed stream. Satzer and coworkers has recently shown that addition of calcium chloride to mAb conditioned medium containing phosphate will result in the formation of insoluble calcium phosphate that can effectively precipitate DNA . HCP and aggregate levels were also reported to be lower after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Satzer and coworkers has recently shown that addition of calcium chloride to mAb conditioned medium containing phosphate will result in the formation of insoluble calcium phosphate that can effectively precipitate DNA. 32 HCP and aggregate levels were also reported to be lower after treatment. As calcium chloride and phosphate buffers present no regulatory or safety hurdles, calcium phosphate precipitation was evaluated as an aggregate removal technique for scFv-IgG bispecific antibodies.…”
Section: Non-chromatographic Clarification Technologies (Calcium Phosmentioning
confidence: 97%
“…Two precipitation protocols consisting of precipitation agents CaCl 2 and caprylic acid were recently published . Addition of CaCl 2 to a cell culture supernatant (with a certain threshold PO 4 3‐ concentration) has been reported to result in formation of insoluble calcium phosphate precipitate which causes co‐precipitation of dsDNA and reduction in HCP concentration . In caprylic acid (octanoic acid, C 8 H 16 O 2 ) precipitation at low pH, the hydrophobicity of the octyl moiety causes acidic proteins in the solution to precipitate .…”
Section: Resultsmentioning
confidence: 99%
“…In caprylic acid (octanoic acid, C 8 H 16 O 2 ) precipitation at low pH, the hydrophobicity of the octyl moiety causes acidic proteins in the solution to precipitate . Plasma product manufacturers have long utilized this method for effective precipitation of non‐immunoglobulin proteins from serum, plasma, and ascites fluid .…”
Section: Resultsmentioning
confidence: 99%
“…A starting phosphate concentration of > 4 mM has been found to promote efficient flocculation of double stranded DNA (dsDNA) [28]. The phosphate concentration of the CCCS was therefore determined and phosphate levels were found to be sufficient (4.4 ± 0.1 mM).…”
Section: Methodsmentioning
confidence: 99%